THE JAIL AND ITS METHODS, FACE TO FACE WITH THE DELINQUENT - Mirela Cristiana NILĂ STRATONE (Challenges of the Knowledge Society, 2014)
The Jail has evolved over time thanks to various critics brought to the address of the two purposes: custody and reeducation. Of course, the custody and the reeducation have functioned on the basis of specific methods. In their turn, these methods have suffered critics, which led to change in penitentiary system. The prison's methods have evolved in the sense of respecting the human rights, of positive moral values as well in the culturalization purpose of those in detention. The prison conditions change at the same time with the society and social values are projected on prison life. The current study refers to the issues related to setting up of prisons in Romania and at the seven optimal conditions of the prison life, as a first step towards a more complex work, about a analysis of costs between detention and alternatives to the sentence with imprisonment.